2021
DOI: 10.1002/fee.2379
|View full text |Cite
|
Sign up to set email alerts
|

Parasites of the past: 90 years of change in parasitism for English sole

Abstract: Historical data are extremely rare but essential for ascertaining whether contemporary infectious disease burdens are unusual. Natural history collections are a valuable source of such data, especially for reconstructing long timelines of parasite abundance. We quantified the parasites of 109 museum specimens of English sole (Parophrys vetulus), an economically important flatfish, collected from Puget Sound, Washington, over a 90-year period (1930-2019). We counted nearly 2,500 individual parasites representin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…The parasite taxa collected have both complex and direct life cycles and demonstrate no clear patterns of presence or absence corresponding to life-cycle type, host species use or higher taxonomic group. Similarly, with an exception for the Acanthocephala, Welicky et al (2021) found no correlation between life cycle or taxonomic group and changes in abundance of English Sole parasites. Future work should identify natural and anthropogenic disturbances and investigate the routes through which they alter parasite communities of English Sole in the Salish Sea.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The parasite taxa collected have both complex and direct life cycles and demonstrate no clear patterns of presence or absence corresponding to life-cycle type, host species use or higher taxonomic group. Similarly, with an exception for the Acanthocephala, Welicky et al (2021) found no correlation between life cycle or taxonomic group and changes in abundance of English Sole parasites. Future work should identify natural and anthropogenic disturbances and investigate the routes through which they alter parasite communities of English Sole in the Salish Sea.…”
Section: Discussionmentioning
confidence: 78%
“…Please refer to Welicky et al . (2021) to see the analyses of changes in abundance for each taxon and higher taxonomic group. Whole species names are given in Table A1.…”
Section: Fig A1mentioning
confidence: 99%
See 1 more Smart Citation
“…We sourced fluid-preserved fish specimens from natural history collections across North America and performed a modified parasitological dissection that minimizes damage to these irreplaceable specimens while maximizing our ability to visually detect parasites ( 18 , 38 ). For each host species–decade combination between 1920 and 2020, we dissected a median of 9.5 fish individuals (range = 0 to 20; SI Appendix , Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Parasite taxonomic identifications should be as highly resolved as possible and—because most of these specimens have been fixed in formalin—we often cannot rely on sequencing to achieve this. In the ‘parasites of the past’ project, we stained, mounted and cleared parasites to better visualize diagnostic features and we partnered with a parasite taxonomist to achieve high taxonomic resolution through strictly morphological identification (Welicky et al, 2021; Wood et al, in review). Derivative specimens (e.g.…”
Section: The Constraints and Responsibilities Of Extracting Parasitol...mentioning
confidence: 99%